El conocimiento declarativo como un parámetro de medida de la solución mental en escolares de ambos sexos de 4º, 5º y 6º grado y su relación con los juegos deportivos colectivos (2010)
ABSTRACT: In this paper we compare and analyze differences between male and female school students concerning the ability to make decisions in a simulated situations, where the motor component is absent. The sample was made up of 60 individuals (30 boys and 30 girls) between 11 and 14 years of age. Each individual was tested in a situation which required their observation and assessment ability in the game situation in order to assess the individual ability associated to the solution of a tactical and strategic problem in a game situation. Such an ability was assessed using a system including watching a videogram. Children were selected randomly. Measurement instruments were designed by researchers and data were processed using the chi-square test. To manage information a chi-square test (c2) was used, in order to find existing differences in the frequency of categories used. t-Student variable was also used to compare average values of V-F by gender, a F Fischer to compare each group. Results show most of the students made correct decisions (80%), which indicates a good understanding of the concept of passing to the best situated player. Differences between genders were not significant, yet results show some differences between grades. According to the results we can conclude that the evaluated children had a good discriminatory capacity and paid attention (focused) to the best placed individual to receive the pass, which is reflected in an ability to make good decisions in game situations.